2020
DOI: 10.7759/cureus.7831
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Psoriasiform Dermatitis Following Dupilumab Use for Autoeczematization Secondary to Chronic Stasis Dermatitis

Abstract: T helper 2 (Th2) and T helper 1 (Th1) mediated immune processes lie on a spectrum. Autoeczematization secondary to chronic stasis dermatitis may fall on the Th2 side of the spectrum due to skin stretch and chronic barrier dysfunction, supporting a primary Th2 response to self-antigen. In our patient, we posited that dupilumab would benefit autoeczematization secondary to chronic stasis dermatitis given its efficacy in atopic dermatitis, a Th2-mediated immune process. We report a case of clinical psoriasiform d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…We discuss these topics in the next chapter. Furthermore, psoriasiform reaction during dupilumab treatment has been reported ( Fowler et al., 2019 ; Napolitano et al., 2019 ; Schrom et al., 2020 ) with increased expression of IL-23A in the lesional skin ( Napolitano et al., 2021 ). Arthritis and enthesitis during dupilumab treatment have also been reported ( Bridgewood et al., 2021 ; de Wijs et al., 2020c ; Ishibashi et al., 2020 ; Komaki et al., 2021 ; Willsmore et al., 2019 ).…”
Section: Effectiveness and Safety Of Dupilumab For Ad In The Real Worldmentioning
confidence: 99%
“…We discuss these topics in the next chapter. Furthermore, psoriasiform reaction during dupilumab treatment has been reported ( Fowler et al., 2019 ; Napolitano et al., 2019 ; Schrom et al., 2020 ) with increased expression of IL-23A in the lesional skin ( Napolitano et al., 2021 ). Arthritis and enthesitis during dupilumab treatment have also been reported ( Bridgewood et al., 2021 ; de Wijs et al., 2020c ; Ishibashi et al., 2020 ; Komaki et al., 2021 ; Willsmore et al., 2019 ).…”
Section: Effectiveness and Safety Of Dupilumab For Ad In The Real Worldmentioning
confidence: 99%
“…Furthermore, one record of a patient with EE associated with a common variable immunodeficiency (CVID) demonstrated complete resolution of skin manifestations within 8 weeks [ 83 ]. Secondary generalized eczematization in a patient with underlying chronic venous stasis dermatitis was treated with dupilumab which led to significant improvement of itch; however, new psoriasiform lesions developed subsequently and dupilumab was discontinued [ 84 ].…”
Section: Resultsmentioning
confidence: 99%
“…Patients with chronic stasis dermatitis are at a 37% lifetime risk of developing autoeczematization later in the course of the disease when compared to the general population [ 4 , 6 ]. We postulate that stasis dermatitis causes a reaction involving T cells in the absence of interferon signaling, an autoeczematization reaction.…”
Section: Discussionmentioning
confidence: 99%
“…Identification of T cell-mediated processes as the pathology underlying autoeczematization has helped tailor treatment. A study on dupilumab, a monoclonal antibody inhibitor of IL-4 receptor, as a treatment for autoeczematization found that this treatment shifted the T cell-mediated reaction towards Th1 dominance, rather than Th2, causing a subsequent resolution of the autoeczematous rash and development of a psoriatiform rash that was different from the initial autoeczematous rash [ 6 ]. This finding guides the choice of methotrexate as a treatment.…”
Section: Discussionmentioning
confidence: 99%